Groebke–Blackburn–Bienaymé multicomponent reaction coupled with unconventional Pictet–Spengler cyclization for the synthesis of imidazo[4, 5‐b]pyridine fused polycyclic heterocycles. (13th January 2022) - Singh, Rahul; Kumar, Ravinder; Kaur, Manpreet; Patil, Madhuri T.; Sahoo, Subash Chandra; Salunke, Deepak B.
Abstract: A diverse library of fused tetracyclic and pentacyclic imidazo[4, 5‐ b ]pyridine scaffolds was synthesized using an unconventional strategy, involving Groebke–Blackburn–Bienaymé (GBB) multicomponent reaction coupled with Pictet–Spengler (PS) cyclization. The reaction strategy involves the use of 2‐aminoazine, aldehyde, and 1, 1, 3, 3‐tetramethyl butyl isocyanide in the GBB reaction followed by the dealkylation to generate a free amine, which on PS cyclization with another aldehyde generated a fused polycyclic heterocycle. A small set of 15 diverse polycyclic heterocycles were synthesized and their structures were confirmed by 1 H NMR, 13 C NMR, and mass spectrometric analyses. In addition, a single‐crystal X‐ray diffraction of one of the library members established the three‐dimensional structure of the polycyclic skeleton. Abstract :